Good Sex, Bad Sex Preljocaj's Le Sacre du printemps and Ek's Carmen - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2002)
More Rites: Preljocaj's Printemps and Ek's Carmen. PALABRAS CLAVE: Le Sacre du printemps, Mats Ek, Carmen, Angelin Preljocaj.